Speckle-tracking echocardiography elucidates the effect of pacing site on left ventricular synchronization in the normal and infarcted rat myocardium. - Michal Mor (Public Library of Science (PLoS), 2014)
Background Right ventricular (RV) pacing generates regional disparities in electrical activation and mechanical function (ventricular dyssynchrony). In contrast, left ventricular (LV) or biventricular (BIV) pacing can improve cardiac efficiency in the setting of ventricular dyssynchrony, constituting the rationale for cardiac resynchronization therapy (CRT). Animal models of ventricular dyssynchrony and CRT currently relay on large mammals which are expensive and not readily available to most researchers. We developed a methodology for double-site epicardial pacing in conscious rats. Here, following post-operative recovery, we compared the effects of various pacing modes on LV dyssynchrony in normal rats and in rats with ischemic cardiomyopathy. Methods Two bipolar electrodes were implanted in rats as follows: Group A (n = 6) right atrial (RA) and RV sites; Group B (n = 7) RV and LV sites; Group C (n = 8) as in group B in combination with left coronary artery ligation. Electrodes were exteriorized through the back. Following post-operative recovery, two-dimensional transthoracic echocardiography was performed during pacing through the different electrodes. Segmental systolic circumferential strain (Ecc) was used to evaluate LV dyssynchrony. Results In normal rats, RV pacing induced marked LV dyssynchrony compared to RA pacing or sinus rhythm, as measured by the standard deviation (SD) of segmental time to peak Ecc, SD of peak Ecc, and the average delay between opposing ventricular segments. LV pacing and, to a greater extend BIV pacing diminished the LV dyssynchrony compared to RV pacing. In rats with extensive MI, the effects of LV and BIV pacing were markedly attenuated, and the response of individual animals was variable. Conclusions Rodent cardiac pacing mimics important features seen in humans. This model may be developed as a simple new tool to study the pathophysiology of ventricular dyssynchrony and CRT.